State and problems training, advanced training and retraining in the field of land planning - Tretiak, A.; Tretiak, V.; Pendzey, L. (Land Management, Cadastre and Land Monitoring, 2017)
Scientific and technological progress and improve land relations, land use and organization of work makes the need for systematic improvement of forms and methods of preparation, training and retraining in the land. Training in the land - is the formation of staff knowledge and skills in a particular professional field, that training people who want to get a profession in the field of land relations and the use and protection of land and other natural resources. In this connection the question the quality of the professionals who work in the system of land and land management enterprises. So in recent years, the system of land worked by 25 thousand. People .. to 28 thousand. People. The number of employees of DerzhzemahenstvaUkraine(and today DerzhheokadastruUkraine) ranged from 9.5 - 10 thousand. People. Thus, in stateenterprisesLandManagement Institute, Centre of state land cadastre and land management of private enterprises and entrepreneurs are about 18 thousand. People. In the system of fixed services is almost 90% of workers with higher education. But of these, only about about 70% have higher education universities III-IV accreditation levels, and only about 50% - land management. Managers and professionals who have land management and land use close to education up together with the Bachelor education only 64% of the total number of employees. Thus, the problem of professional education in the field of land is very relevant. It is necessary to consider further training of land-management education for integrated communities. The article is justification for expanding areas of training in the field of land management and the introduction of new professions (specializations) and the management of natural areas. According to Article 66 of the Law of Ukraine "On Land Management" of 22.05.2003 number 858-IV, professional activities in the field of land may engage citizens with special higher education levels and appropriate professional guidance. Cabinet of Ministers of Ukraine on April 29, 2015 № 266 determined instead specialties "Land Management and Cadastre" and "assessment of land and property" - specialty "Geodesy and Land Management" which referred to the field of knowledge "Architecture and Construction", which refers to the engineering sciences . However, the definition of land according to the law ofUkraine"On Land Management" activities in the field of land management and land use documentation content, a specialty of the land should belong to the natural sciences or management. Search discourse of the theory of Land Management shows that there are many concepts and categories in the field of land management in particular, such as "innovations in land management", "economy land", "Legal Land Management", "technical land management", "cadastral survey", "ecological land management" "social Land Management", "Land Management design." Absolute champion mentions in the Internet Google is "land economics" (494 thousand. Mentions), followed by "technical land management" (487 thousand. References). It noted widespread references in the search engine world for Ukraine Yandex.ua term "cadastral survey" (6 million. Mentions), followed by "technical land management" (5 million. References), legal, social and environmental land management by 4 million. Mentions. Is ambiguous definition of recurrence frame "ecological economy" and «Ecological and economic land management». Thus, according Yandex.ua, leader of «Ecological and economic land management» (8 million. Mentions) and the version of Google.com leader «Ecological and economic land management» (3 million. References). This communication should focus that the terms in English prevail in times of recurrence in the same terms in Ukrainian or Russian. In this regard, in our view, training in land management, inventory, assessment and land protection must be understood as education relevant educational qualification (Bachelor, Master) in "Architecture and Construction" (code 19), " Management and administration "(code 07)," Natural Science "(code 10) and professions (specializations) related to professional management, environmental, economic, scientific and other activities consisting of the central and local authorities, enterprises, institutions and organizations regardless of ownership. At present the main problems of preparation, training and retraining in the field of land management are the lack of a systematic approach to funding, standardization organization and implementation of educational and research activities in the field of land management, inventory and appraisal and land protection, expansion professions (specializations) related with administrative, environmental, economic, scientific and other activities in the field of land management. It is proposed to expand the training of specialists in the field of land appropriate educational qualification (Bachelor, Master) in "management and administration" (code 07), "Natural Science" (code 10) and professions (specializations) related to professional management, environmental, economic, scientific and other activities. Keywords. Directions of training, specialties in land management sciences.